IMPROVING THE WELFARE OF FISHERMEN ENTREPRENEURS IN NEW NORMAL ERA WITH INCLUSIVE FINANCING MODEL THROUGH VILLAGE CREDIT INSTITUTIONS - Made Kembar Sri BUDHI; Ni Nyoman Reni SUASIH; Ni Putu Nina Eka LESTARI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The Covid-19 pandemic has had a domino effect on various sectors, both macro and micro. Traditional fishermen in Kedonganan Village (which is a coastal area and a well-known tourist destination in Bali) have also experienced a decline in tourism activities, especially related to limited funding. The purpose of this research is to improve the welfare of fishery entrepreneurs in Kedonganan Village after Covid-19 through an inclusive financing model in the perspective of the Village Credit Institution. This type of research is qualitative research by analyzing data with existing theories to dissect research problems. The data analysis technique used in this research is qualitative data analysis. Based on the results of data analysis, it can be concluded that traditional fishermen in Kedonganan Village feel helped by financial assistance (capital) for individuals, but cannot be given to fishing groups because they do not have formal legal elements. The beneficiary fishermen also stated their readiness to increase their business, one of which was through increasing working time, so that credit installments could be paid. In addition, the assistance of fishing gear facilities and infrastructure (including software applications) as well as institutional empowerment has been able to improve the welfare of fishery entrepreneurs.